Drug Policies and Development Conflict and Coexistence - Buxton, Julia; Chinery-Hesse, Mary; Tinasti, Khalid (International Development Policy, 2020)
The 12th volume of International Development Policy explores the relationship between international drug policy and development goals, both current and within a historical per-spective. Contributions address the drugs and development nexus from a range of critical viewpoints, highlighting gaps and contradictions, as well as exploring strategies and oppor-tunities for enhanced linkages between drug control and development programming. Crim-inalisation and coercive law enforcement-based responses in international and national level drug control are shown to undermine peace, security and development objectives. Readership: Academic scholars and researchers, policymakers and development practitioners interested in international development policy, drug policies and their effects on development, global economic and political trends, and local development issues.